The Use of MURDER Strategy to Improve Students’ Reading Comprehension - Syamsia, S (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
The aim of this research was to find out how the use of MURDER strategy can improve students' reading comprehension at SMP Islam 2 Kota Ternate. The researcher used Classroom Action Research (CAR) to conduct this research. There were 22 students as a subject. There were two cycles, each cycle consisted of two meetings. Based on the description of the research results and discussion, it was concluded that implementing the MURDER strategy can improve students' reading comprehension. In the first cycle, only two students achieve a passing grade, meaning 90.9% of students studying at the SMP Islam 2 Kota Ternate failed the passing exam. In the second cycle, however, only 13.63% of students failed to get a passing grade. This means that in the second cycle, 19 students met the success criteria and only 3 students did not yet meet the success criteria. This means that the reading comprehension of students at SMP Islam 2 Kota Ternate has improved significantly compared to the reading literacy teaching and learning process before the implementation of the MURDER. strategy.